Human occupation at Jinmium, northern Australia : 116,000 years ago or much less? - Spooner, N. A.
The rock-shelter of Jinmium in the Northern Territory of Australia hit the headlines a year-and-a-half ago when TL dates suggested human occupation might date from 116,000 years ago. Such dates were much earlier than any previously obtained for Australia, and thus suggested the continent was colonized at a very early stage in human dispersal around the Pacific. However, some TL dating is notoriously difficult to interpret, and here Nigel Spooner has re-assessed one of the later dates in the Jinmium sequence. His interpretation calls into doubt some of the earlier claims.